Are all bony fishes oxygen regulators? Evidence for oxygen regulation in a putative oxygen conformer, the swamp eel Synbranchus marmoratus. Issue 1 (28th January 2019) - Svendsen, Morten Bo Søndergaard; Johansen, Jacob L.; Bushnell, Peter G.; Skov, Peter V.; Norin, Tommy; Domenici, Paolo; Steffensen, John F.; Abe, Augusto
Abstract : This study investigated the oxygen consumption of the putative oxygen conformer marbled swamp eel Synbranchus marmoratus during progressive hypoxia. Earlier studies have not reached an agreement on whether S. marmoratus is a conformer or a regulator. Our results support the view that S. marmoratus is an oxygen regulator, like most bony fishes.